Assessment of clinical methods and ultrasound in predicting fetal birth weight in term pregnant women - Yadav, Ruby; Sharma, Barun Kumar; Deokota, Ritu Nath; Rahman, Hafizur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Birth weight is the greatest single factor in the survival of fetus and important factor of neonatal problems. Thus estimating fetal weight antenatally is important to the obstetricians to prevent respiratory morbidity and anticipate problems of shoulder dystocia. The objectives of this study were to assess the fetal weight in term pregnancies by various clinical methods and Ultrasound and to correlate these methods of estimation of fetal weight with the actual birth weight of the baby after delivery. Methods: Between January 2013 to June 2014 a prospective cross-sectional hospital based study was conducted at the Department of Obstetrics and Gynaecology of Central Referral Hospital, Sikkim Manipal Institute of Medical Sciences Gangtok. All subjects with singleton pregnancy with reliable date/dating scan, with no fetal anomalies, undergoing obstetric scan at term one week prior to delivery were included. Estimated fetal weight (EFW) was calculated by clinical method AG×SFH (Abdominal girth x Symphysiofundal height) and Johnson’s formula. Hadlock formula using Ultrasound was used. EFW were compared with the actual birth weight. Results: Two hundred women were recruited during the study period. Mean age of the women were 25.24 ±3.32 years and mean gestational age was 38.83 ± 1.10 weeks. For all the cases scan delivery interval was less than seven days. Sixty nine percent of birth weights were distributed between 2000-3500 grams. Mean birth weight of Hadlock’s formula (3240 grams) was closest to the mean of actual birth weight (3100 grams). Hadlock Formula was more accurate for birth range between 2500-3500 grams followed by AG×SFH. For Large for Gestational age babies Johnson’s Formula was found to be better. Average error in estimating fetal weight was 190.34 grams by Hadlock’s formula, 208.78 grams by AG x SFH and 290.29 grams by Johnson’s method. The difference between Hadlock’s and AG×SFH was not statistically significant (p>0.01); but for Johnson’s it was statistically significant (p<0.01). Prediction of birth weight within 10% of actual birth weight was in 81% of Cases by AG x SFH formula, 79% by Hadlock’s formula, and 47% by Johnson’s formula. Conclusions: Clinical estimation of birth weight clearly has a role in management of labour and delivery in a term pregnancy. Clinical estimation especially by SFH×AG method is as accurate as routine USG estimated in average birth weight. SFH × AG clinical formula can be of great value in developing countries like ours, where ultrasound is not available at many health care centers especially in a rural area.